2014
DOI: 10.1038/nrn3785
|View full text |Cite
|
Sign up to set email alerts
|

Functional organization of the hippocampal longitudinal axis

Abstract: The precise functional role of the hippocampus remains a topic of much debate. According to a dominant view, the dorsal/posterior hippocampus is implicated in memory and spatial navigation and the ventral/anterior hippocampus mediates anxietyrelated behaviours. However, this 'dichotomy view' may need revision. Gene expression studies demonstrate multiple functional domains along the hippocampal long axis, which often exhibit sharply demarcated borders. By contrast, anatomical studies and electrophysiological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

120
1,425
10
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,438 publications
(1,563 citation statements)
references
References 197 publications
(258 reference statements)
120
1,425
10
8
Order By: Relevance
“…However, other pathologies may contribute to the cognitive symptoms of DLB and should be investigated further; one study has previously observed that cognitive decline in LBD may be a consequence of alpha‐synuclein, amyloid‐beta and phosphorylated tau pathology (Howlett et al, 2015), and additionally, one study of the medial temporal lobe showed that alpha‐synuclein pathology, rather than AD pathology, had a role in the atrophy of the amygdala (Burton et al, 2012). Hippocampal volume showed the strongest association with the CAMCOG memory score, which is in keeping with the memory function of the hippocampus (Eichenbaum, 2004; Strange et al, 2014). These results also indicate that atrophy to adjacent medial temporal lobe subregions can also influence the DLB cognitive phenotype, with an overlap of symptoms: parahippocampal surface thickness was associated with CAMCOG cognition and memory subscores, but not executive function, the entorhinal surface thickness was associated with total CAMCOG scores, as well as CAMCOG memory and executive function subscores.…”
Section: Discussionsupporting
confidence: 66%
“…However, other pathologies may contribute to the cognitive symptoms of DLB and should be investigated further; one study has previously observed that cognitive decline in LBD may be a consequence of alpha‐synuclein, amyloid‐beta and phosphorylated tau pathology (Howlett et al, 2015), and additionally, one study of the medial temporal lobe showed that alpha‐synuclein pathology, rather than AD pathology, had a role in the atrophy of the amygdala (Burton et al, 2012). Hippocampal volume showed the strongest association with the CAMCOG memory score, which is in keeping with the memory function of the hippocampus (Eichenbaum, 2004; Strange et al, 2014). These results also indicate that atrophy to adjacent medial temporal lobe subregions can also influence the DLB cognitive phenotype, with an overlap of symptoms: parahippocampal surface thickness was associated with CAMCOG cognition and memory subscores, but not executive function, the entorhinal surface thickness was associated with total CAMCOG scores, as well as CAMCOG memory and executive function subscores.…”
Section: Discussionsupporting
confidence: 66%
“…In contrast, more posterior hippocampal projections in the fornix include the dense inputs to the mammillary bodies (Christiansen, Dillingham, et al., 2016). It should, however, be emphasized that in the rat and macaque brains these distinctions are relative, that is, there is a gradient in the anterior–posterior inputs from the subiculum and CA1 rather than a sharp division between the anterior and posterior hippocampus (Aggleton, 2012; Barbas & Blatt, 1995; Evensmoen et al., 2015; Kjelstrup et al., 2008; for review see Strange et al., 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Of the two areas, the anterior hippocampus has been more linked to stress, anxiety, and emotional processing (Bannerman et al., 1999; Chase et al., 2015; O'Mara, 2005), whereas the posterior hippocampus is more typically linked to fine‐grain spatial processing (Poppenk et al., 2013; Strange et al., 2014). These differences do not, however, reflect a dichotomy, rather a gradation of change along the anterior–posterior axis (Collin et al., 2015; Poppenk et al., 2013; Strange et al., 2014). One interpretation is that the anterior hippocampus is important for forming large‐scale representations of the environment, whereas the posterior hippocampus provides more detailed representations (Poppenk et al., 2013; Strange et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations